A prophylactic effect of proprioceptive neuromuscular facilitation (PNF) stretching on symptoms of muscle damage induced by eccentric exercise of the wrist extensors - Peanchai Khamwong (2018)
Stretching with proprioceptive neuromuscular facilitation (PNF) is frequently used before exercise. The prophylactic effect of PNF on symptoms of muscle damage induced by eccentric exercise of the wrist extensors was examined in this study. Twenty-eight healthy males were randomly divided into the PNF group (n = 14) and the control group (n = 14). PNF was used before eccentric exercise induction in the wrist extensors. All subjects were tested to examine muscle damage characteristics including sensory-motor functions at baseline, immediately, and from 1st to 8th days after the exercise-induced muscle damage (EIMD). The results demonstrated that the PNF group showed a lesser deficit in some sensory-motor functions (p < 0.05) than the control group. The prior PNF stretching application could be useful for attenuating the signs and symptoms of muscle damage after eccentric exercise. © 2010 Elsevier Ltd.